(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In this paper author defines the concepts about Q-I vague sets, Q-I vague subnear-ring, Q-I vague ideals, homomorphic image and pre-image of Q-I vague ideals in a near-ring R.